Synthesis and Physiochemical Properties of Sulphated Tamarind (Tamarindus indica L.) Seed Polysaccharide - Sabrina Ziliani; Anna Alekseeva; Carlo Antonini; Emiliano Esposito; Fabio Neggiani; Marco Sansò; Marco Guerrini; Sabrina Bertini (Molecules)
Tamarind seed polysaccharide (TSP) is a neutral water-soluble galactoxyloglucan isolated from the seed kernel of Tamarindus indica with average molecular weight (Mw) 600–800 kDa. The high viscosity of TSP slows solubilisation, and the absence of charged substituent hinders the formation of electrostatic interactions with biomolecules. TSP was sulphated in a one-step process using dimethylformamide as a solvent, and sulphur trioxide-pyridine complex as a sulphating reagent. Studies of chemical structure, molecular weight distribution and viscosity were conducted to characterise the synthesised products. The sulphation degree was established by conductimetric titration; the sulphate group distribution was studied by NMR spectroscopy and liquid chromatography-mass spectrometry, and sulphated TSP oligomers were obtained by enzymatic degradation with cellulase and/or xyloglucanase. Sulphated products showed higher solubility than TSP, Mws in the range of 700–1000 kDa, a sulphation degree of two to four per subunit and pseudoplastic behaviour. A preliminary study of mucoadhesion revealed the unexpected interaction of S-TSP with mucin, providing a route by which sulphated TSP interactions with biomolecules may be influenced.